The Significance and Limitations of Pre- and Postnatal Imaging in the Diagnosis and Management of Proximal Focal Femoral Deficiency - Aaron C. Llanes; Emma Venard; Sean Youn; Dane Van Tassel; Luis F. Goncalves; Mohan V. Belthur (Diagnostics)
Background and Clinical Significance: Proximal femoral focal deficiency (PFFD), also referred to as congenital femoral deficiency, is a longitudinal limb deficiency and birth defect that affects the lower extremity including the hip and femur, resulting in a deformed and shortened limb. It can be diagnosed and classified using a combination of imaging modalities, including radiographs, ultrasonography, magnetic resonance imaging and computerized tomography. It is crucial to characterize this birth defect in the prenatal period to appropriately prepare parents through counseling. Postnatal imaging should be performed to confirm the diagnosis, prognosticate and predict the patient’s course for treatment and management. Close follow-up and family/patient-centered care contribute to optimized patient outcomes. Case Presentation: Here, we present a series of three cases of varying PFFD severity and presentation, detailing the evaluation process, the limitations and value of imaging, and the treatment outcomes of these patients. Each case has a different PFFD classification and treatment strategy that we utilized according to the data that we attained through continuous patient care and discussion. Conclusions: We highlight the difficulties in identifying and classifying PFFD in the prenatal period while demonstrating how postnatal imaging clarified the diagnosis and informed appropriate counseling and treatment. Close follow-up and the length of patient continuity allowed us to maximize patient outcomes despite the variety in PFFD presentation and severity.